(untitled) (Global Journal of Human-Social Science, 2017)
Asian Americans represent the fastest-growing best-educated and highest-income demographic in the United States The successful status of Asians Americans is reflected in the fact that they are collectively associated with a model minority stereotype that characterizes them in terms of traits such as their being academically-oriented high-achieving studious law-abiding and hard-working Yet despite the apparent success of Asians Americans as a whole and the positive stereotypes associated with this minority compared to other women of color Asian women are significantly less likely to hold leadership positions This study attempts to understand the reason for this gap Using a grounded theory methodology this study explores the live experiences of 16 Asian American female middle managersin order to understand the influence of ethnicity and gender on their leadership experiences and career opportunities The study s results reveal that the participants had complex and conflicting experiences that resulted in both opportunities and challenges Participants sometimes benefited from the positive associations of their Asian ethnicity with qualities such as intelligence and diligence and sometimes they face the demerits of being Asians that reinforce a view of them being passive and lacking in leadership skills Research also reveals the impact of gender identity over the career of working women The study also shows that because of being women and those too from a minority the Asian working women face difficulties in becoming part of local culture That is there exists an insider culture within corporate America that up-holds the importance of male-oriented leadership qualities and that does not allow Asian-American females to become a part of it